Additional records of the genus Colletes Latreille (Hymenoptera: Apoidea: Colletidae) from Siberia, with a checklist of Russian species - Proshchalykin, Maxim Yu.; Kuhlmann, Michael (Zootaxa, 2015)
In addition to a previously published study about Siberian Colletes species, we here further report on poorly known species. Twenty six species are currently known from Siberia with C. cinerascens Morawitz 1893, C. kaszabi Kuhlmann 2002, and C. ebmeri Kuhlmann 2002 found in Russia for the first time and C. wacki Kuhlmann 2002 is newly recorded from the Asian part of Russia. The male of C. wacki is here described for the first time and a lectotype designated for the closely related C. conradti Noskiewicz 1936 to clarify the taxonomy of this group. Colletes uralensis Noskiewicz 1936 was erroneously recorded from Russia and is removed from the list of Russian species. Images and updated distribution maps are provided for the closely related C. kaszabi and C. uralensis as well as for C. conradti and C. wacki to facilitate their identification. An updated checklist of the 42 species of Colletes so far known from Russia is provided.